BUILDING COMPETITIVE ADVANTAGE IN THE DISRUPTIVE ERA IN ISLAMIC SCHOOLS - Abdul Rasyid Hamami; Nunu Mahnun (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze strategies for building competitive advantage in Islamic schools in the disruptive era characterized by rapid digital technological development and changing societal demands. The main problems faced include the limited ability of institutions to differentiate educational services, implement innovation, and integrate Islamic values into modern management practices. This study employs a quantitative approach with an explanatory design through a survey involving 150 respondents, consisting of principals, teachers, and educational staff. The research instrument was developed based on the resource-based view and educational innovation theories. Data analysis was conducted using SEM-PLS to examine the relationships among variables. The results indicate that educational innovation, strategic leadership, and the integration of Islamic values have a significant effect on competitive advantage. These findings highlight that Islamic educational institutions capable of managing unique resources based on values and technology tend to achieve higher competitiveness. This study contributes theoretically by developing a competitive advantage model grounded in Islamic values and provides practical implications for educational managers in responding to disruptive changes.